Analisis Perencanaan dan Pengendalian Biaya pada Proyek Normalisasi Saluran Drainase Pasar Wadung Asri - Qisthosin, Rikza; Pulansari, Farida (Universitas Batanghari Jambi, 2024)
Normalizing the drainage channels of the Wadung Asri market is a program created by the Sidoarjo Regency government with the condition that the price offered is IDR. 967,769,587.09. The company's level of success in carrying out construction projects can be assessed by an in-depth understanding of how much construction costs are required. To maintain the company's survival, it must obtain sustainable income and even generate profits. This quantitative study aims to obtain project budget data that has been prepared in a systematic and objective manner, with an evaluation aimed at checking the extent to which the budget that has been prepared is compared with the costs that have been realized. This research involves various kinds of data including self-estimated prices (HPS), company budget plans (RAB), unit prices of work, and realistic costs incurred. The collected data was analyzed using the variance analysis method by comparing the company's planned cost budget and the realistic costs of each job description, whether favorable or unfavorable. This research informs us that the company did not suffer a loss but made a profit of 2.88% or IDR 23,180,000.00 from the proposed budget of IDR. 804,924,396.50. Following up on the findings of this research, cost planning and control must be further optimized through collecting work unit price data for each job description in more detail and detail, then research must also be carried out periodically.